A review on MXene-based nanomaterials as adsorbents in aqueous solution. (December 2020) - Jeon, Minjung; Jun, Byung-Moon; Kim, Sewoon; Jang, Min; Park, Chang Min; Snyder, Shane A.; Yoon, Yeomin
Abstract: Environmental pollution has intensified and accelerated due to a steady increase in the number of industries, and finding methods to remove hazardous contaminants, which can be typically divided into inorganic and organic compounds, have become inevitable. One of the widely used water treatment technologies is adsorption and various kinds of adsorbents for the removal of inorganic and organic contaminants from water have been discovered. Recently, MXene, as an emerging nanomaterial, has gained rapid attention owing to its unique characteristics and various applicability. Particularly, in the area of adsorptive application, MXene and MXene-based adsorbents have shown great potential in a large number of studies. In this regard, a comprehensive understanding of the adsorptive behavior of MXene-based nanomaterials is necessary in order to explain how they remove inorganic and organic contaminants in water. Adsorption by MXene-based adsorbents tends to be highly influenced by not only the physicochemical properties of these adsorbents but also water quality, such as pH value, temperature, background ion, and natural organic matter. Therefore, in this review paper, the effect of various water quality on the adsorption of inorganic and organic contaminants by various types of MXene and MXene-based adsorbents is explored. Furthermore, this review also covers general trends in the synthesis of MXene and regeneration of MXene-based adsorbents in order to assess their stability. Highlights: Removal of inorganic and organic contaminants by MXene-based nanomaterials was reviewed. Valuable information was provided for applications of MXene-based nanomaterials in wastewater treatment. Areas of future research for the removal of various contaminants in MXene-based nanomaterials were suggested.